Comparison of the crystal structures of 4,4′-bis[3-(4-methylpiperidin-1-yl)prop-1-yn-1-yl]-1,1′-biphenyl and 4,4′-bis[3-(2,2,6,6-tetramethylpiperidin-1-yl)prop-1-yn-1-yl]-1,1′-biphenyl - Anqi Wan; Narsimha Reddy Penthala; E. Kim Fifer; Sean Parkin; Peter A. Crooks (Acta Crystallographica Section E: Crystallographic Communications, 2015)
As part of a comprehensive program to discover α9α10 nicotinic acetylcholine receptor antagonists, the title compounds C30H36N2, (I), and C36H48N2, (II), were synthesized by coupling 4,4′-bis(3-bromoprop-1-yn-1-yl)-1,1′-biphenyl with 4-methylpiperidine and 2,2,6,6-tetramethylpiperidine, respectively, in acetonitrile at room temperature. In compound (I), the biphenyl system has a twisted conformation with a dihedral angle of 26.57 (6)° between the two phenyl rings of the biphenyl moiety, while in compound (II), the biphenyl moiety sits on a crystallographic inversion centre so the two phenyl rings are exactly coplanar. The terminal piperidine rings in both compound (I) and compound (II) are in the chair conformation. In compound (I), the dihedral angles about the ethynyl groups between the planes of the phenyl rings and the piperidine ring N atoms are 37.16 (16) and 14.20 (17)°. In compound (II), the corresponding dihedral angles are both 61.48 (17)°. There are no noteworthy intermolecular interactions in (I), but in (II) there is a small π-overlap between inversion-related molecules (1 − x, 1 − y, 1 − z), with an interplanar spacing of 3.553 (3) Å and centroid-to-centroid separation of 3.859 (4) Å.